Carbapenem-Susceptible OXA-23-Producing Proteus mirabilis in the French Community - Potron, Anaïs (Antimicrob Agents Chemother, 2019)
Nineteen Proteus mirabilis isolates producing the carbapenemase OXA-23 were recovered over a 2-year period in 19 French hospitalized patients, of whom 12 had community onset infections. The isolates exhibited a slightly reduced susceptibility to carbapenems. Whole-genome analysis revealed that all 19 isolates formed a cluster compared to 149 other P. mirabilis isolates. Because of its susceptibility to carbapenems, this clone may be misidentified as a penicillinase producer while it constitutes a reservoir of the OXA-23-encoding gene in the community.